OP0306 Ten Years of Denosumab Treatment in Postmenopausal Women with Osteoporosis: Results from The Freedom Extension Trial. (15th July 2016) - Bone, H.; Brandi, M.; Brown, J.; Chapurlat, R.; Cummings, S.; Czerwinski, E.; Fahrleitner-Pammer, A.; Kendler, D.; Lippuner, K.; Reginster, J.-Y.; Vittinghoff, E.; Daizadeh, N.; et al.
Abstract : Background: Osteoporosis is an important chronic disease, requiring prolonged treatment. Long-term efficacy and safety data are therefore of great importance. Denosumab (DMAb) is used in over 80 countries or administrative districts worldwide for the treatment of postmenopausal women with osteoporosis. The effects of DMAb treatment for up to 10 years have been evaluated in the 3-year FREEDOM study and its 7-year extension. Objectives: Report results through the final year of the FREEDOM extension, representing up to 10 years of continued DMAb treatment. Methods: During the extension, all subjects were to receive 60 mg DMAb every 6 months and calcium and vitamin D daily. In this analysis, the long-term group received 10 years of DMAb treatment (3 years in FREEDOM and 7 years in the extension), and the cross-over group received 7 years of DMAb treatment (3 years of placebo in FREEDOM and 7 years of DMAb in the extension). Results: Of the 4, 550 subjects who entered the extension, 2, 784 (61%) continued to participate at the beginning of year 10. Of these, 2, 212 (80%) have completed their final 10-year visit, 120 (4%) discontinued, and 452 (16%) were ongoing at the time of this submission. In the long-term group, further significant increases in BMD occurred with mean cumulative 10-year gains of 21.6% (lumbar spine) and 9.1% (total hip) from FREEDOM baseline. The cross-over group had mean cumulative 7-year gains of 16.3% (lumbar spine) and 7.3% (total hip) from the extension baseline (Figure 1 ; all P <0.0001 compared with FREEDOM baseline, extension baseline, and previous measurement). Similar and sustained reductions in bone turnover markers were observed in both groups, with the characteristic attenuation of effect at the end of the dosing period. Yearly rates of new vertebral and nonvertebral fractures remained low. Overall incidence rates of adverse events (AEs) and serious AEs were consistent with data reported previously in the extension study. Conclusions: DMAb treatment for up to 10 years was associated with persistent reduction of bone turnover, continued increases in BMD without therapeutic plateau, and low fracture incidence. The benefit/risk profile for DMAb in an aging population of postmenopausal women remains favorable. Acknowledgement: Amgen funded Disclosure of Interest: H. Bone Grant/research support from: Amgen, Merck, Consultant for: Amgen, Merck, Graunenthaler, Speakers bureau: Amgen, M. Brandi Grant/research support from: Alexion, Abiogen, Amgen, Bruno Farmaceutici, Eli Lilly, MSD, NPS, Shire, SPA and Servier., Consultant for: Alexion, Abiogen, Amgen, Bruno Farmaceutici, Eli Lilly, MSD, NPS, Shire, SPA and Servier., J. Brown Grant/research support from: Amgen, Eli Lilly, Novartis, Consultant for: Amgen, Eli Lilly, Speakers bureau: Amgen, Eli Lilly, R. Chapurlat Grant/research support from: Pfizer, Chugai-Roche, Consultant for: Pfizer, Amgen, Bioiberica, S. Cummings Consultant for: Amgen, E. Czerwinski Grant/research support from: Amgen, Speakers bureau: Amgen, A. Fahrleitner-Pammer Grant/research support from: Roche, Consultant for: EliLilly, Speakers bureau: Amgen, EliLilly, Pfizer, MSD, D. Kendler Grant/research support from: Amgen, Lilly, Astrazenica, Astallis, Consultant for: Pfizer, Merck, Lilly, Amgen, Speakers bureau: Lilly, Amgen, GSK, K. Lippuner Consultant for: Amgen, J.-Y. Reginster Grant/research support from: Bristol Myers Squibb, Merck Sharp & Dohme, Rottapharm, Teva, Roche, Amgen, Lilly, Novartis, GlaxoSmithKline, Servier, Pfizer, Theramex, Danone, Organon, Therabel, Boehringer, Chiltern, Galapagos, Consultant for: Servier, Novartis, Negma, Lilly, Wyeth, Amgen, GlaxoSmithKline, Roche, Merckle, Nycomed-Takeda, NPS, I BSA-Genevrier, Theramex, UCB, Asahi Kasei, Endocyte, Speakers bureau: Merck Sharp and Dohme, Lilly, Rottapharm, IBSA, Genevrier, Novartis, Servier, Roche, GlaxoSmithKline, Merckle, Teijin, Teva, Analis, Theramex, Nycomed, NovoNordisk, Ebewee Pharma, Zodiac, Danone, Will Pharma, Amgen., E. Vittinghoff: None declared, N. Daizadeh Shareholder of: Amgen, Employee of: Amgen, A. Wang Shareholder of: Amgen, Employee of: Amgen, P. Dakin Shareholder of: Amgen, Employee of: Amgen, R. Wagman Shareholder of: Amgen, Employee of: Amgen, S. Papapoulos Consultant for: Amgen, Axsome, Merck & Co, Novartis, UCB, Speakers bureau: Amgen, Merck & Co, UCB